Paleoclimatological Context and Reference Level of the 2°C and 1.5°C Paris Agreement Long-Term Temperature Limits - Lüning, Sebastian; Vahrenholt, Fritz (Frontiers in Earth Science, 2017)
The Paris Agreement adopted in December 2015 during the COP21 conference stipulates that the increase in the global average temperature is to be kept well below 2°C above “pre-industrial levels” and that efforts are pursued to limit the temperature increase to 1.5°C above “pre-industrial levels”. In order to further increase public acceptance of these limits it is important to transparently place the target levels and their baselines in a paleoclimatic context of the past 150,000 years (Last Interglacial, LIG) and in particular of the last 10,000 years (Holocene; Present Interglacial, PIG). Intense paleoclimatological research of the past decade has firmed up that pre-industrial temperatures have been highly variable which needs to be reflected in the pre-industrial climate baseline definitions. The currently used reference level 1850-1900 represents the end of the Little Ice Age (LIA).The LIA represents the coldest phase of the last 10,000 years when mean temperatures deviated strongly negatively from the Holocene average and which therefore are hard to justify as a representative pre-industrial baseline. The temperature level reached during the interval 1940-1970 may serve as a better reference level as it appears to roughly correspond to the average pre-industrial temperature of the past two millennia. Placing the climate limits in an enlarged paleoclimatic context will help to demonstrate that the chosen climate targets are valid and represent dangerous extremes of the known natural range of Holocene temperature variability.